TORNAR-SE MÃE NO CONTEXTO DA VIOLÊNCIA SEXUAL: Uma pesquisa em Psicanálise - SILVA, Renata Barreto da (2019)
Sexual violence has been considered a public health issue since 2002 in Brazil, due to its high incidence and resulting health problems. Unplanned pregnancy is the third most prevalent consequence of rape, occurring more frequently among children and teenagers. In the face of pregnancy resulting from sexual violence, women are given three possibilities: legal termination of pregnancy; maintain the pregnancy and insert the child in the family; or maintain the pregnancy and refer the child to care services. The choice to maintain the pregnancy and become the baby’s mother is determined by several factors, occurring uniquely to each woman. Pregnancy is something that implies but does not determine motherhood. Based on Freud and Lacan’s theoretical development, we can read that motherhood is crossed by imaginary and symbolic issues, being built not from the moment the woman finds herself pregnant, but in a previous period, referring to the constitution of female sexuality. We consider this research relevant because it proposes a dialogue between Psychoanalysis and Public Health. The main objective of this research is to discuss the choice of being a mother from the perspective of women with pregnancy resulting from sexual violence. As specific objectives, we seek to identify: factors that contribute to the choice of keep the child by a woman with pregnancy resulting from sexual violence; and the notion of motherhood for that woman. For this discussion, an empirical research based on psychoanalysis was performed. Data collection was done through semi-structured interview script and participant observation. It is noteworthy that, in psychoanalysis research, the construction of knowledge occurs through the inseparability between theory, practice and research, without the purpose of inferring generalizations or closing the questions about the theme, but establishing some articulations in order to take into account the uniqueness of each case. The study was conducted according to what is recommended by Resolutions 466/2012 and 510/2016 of the National Health Council. Thus, in the first chapter we give a contextualization about sexual violence and its resulting pregnancy as a public health problem and a violation of human rights. In the second chapter, by working with texts by Freud and Lacan, as well as articles by contemporary psychoanalysts, we make some considerations about the issue of sexual violence, starting from the articulation between the concepts of aggression and violence. We discuss the constitution of femininity, the choice to become a mother and the constitution of motherhood, and we end the chapter with articulations about adolescent motherhood. In the third chapter, we present the method developed in the research, approaching the type of study, the delimitation of participants and sample, the scenario where the research took place, the techniques and instruments used in data collection, the recommended ethical aspects, the procedures adopted in the study and the data analysis. In the fourth chapter, we expose and discuss the found results, initially characterizing the study participants and then sketching articulations on motherhood for each of them. In order to conclude this paper, in the fifth chapter we outline some considerations through the discussion of issues that permeate the motherhood constitution in the context of the discovery of pregnancy resulting from sexual violence and the choice to keep the pregnancy and take care of the resulting baby.